The doctrine of piercing the corporate veil in South Africa: an analysis of the South African approach with lessons from the Canadian jurisprudence - Bailey, Michael (Department of Commercial Law, 2021)
The first principle of a corporation is the right to have separate legal personality independent from the directors and shareholders. The entity becomes distinct from those who incorporate it and those who participate in the active management of the corporation's business. The corporation is owned by shareholders. The shareholders, as the natural persons with ownership rights in the artificial entity, retain obligations distinct from those of the corporation. The shareholders thus cannot be held liable for obligations that the corporations may be required to fulfil, be it primary or collateral, in its business dealings. There is a separation between the company, as a separate juristic person, and its shareholder. The distinction between the company and its shareholders and directors is described as the infamous ‘veil' to separate the corporation from the owners themselves. The benefit of separate legal personality is the second principle afforded to a corporation - limited liability of shareholders. As a general principle shareholders are not liable for the debts of the company. As a separate legal person the company exists in perpetuity despite changes in ownership structure. This makes commercial sense, because ‘the primary purpose for the doctrine of separate legal personality is to encourage entrepreneurship, by shifting the risks of business failure away from entrepreneurs to creditors and other risk bearers'. Managers of the business can take necessary commercial risks without the consequence of individual liability.